Rethinking education for democracy: a study of co-determination in a Norwegian school - Magerøy, Solveig Maria (Frontiers in Education, 2023)
Abstract Through a two-day intervention in a class of 12-year-olds, this study facilitated lessons where the pupils could themselves decide methods of learning, and themes to focus on, searching for spaces and methods to activate the pupils participatory competencies. National student pupils’ surveys in Norway have repeatedly shown that pupils do not feel as though they can participate in their learning at schools. The pupils in this study reported that they enjoyed this intervention and were ambitious regarding what they wished to achieve. While this may seem irrelevant or superficial at first glance, reflecting on the engagement the pupils expressed, enjoyment of learning may have been the most significant driving force for the pupil’s participation. Indeed, the majority worked in groups with peers and demonstrated ownership of their thematic area and projects. However, a few pupils became insecure and passive when given the opportunity to decide for themselves. The pupils’ ownership, level of ambition, and expert role in their projects indicate that their participatory abilities were activated, thus suggesting the importance of introducing co-determination as a didactical tool in school.